Progressive Loss of Cones in Achromatopsia: An Imaging Study Using Spectral-Domain Optical Coherence Tomography - Thiadens, Alberta A. H. J.; Somervuo, Ville; van den Born, L. Ingeborgh; Roosing, Susanne; van Schooneveld, Mary J.; Kuijpers, Robert W. A. M.; van Moll-Ramirez, Norka; Cremers, Frans P. M.; Hoyng, Carel B.; Klaver, Caroline C. W. (Investigative ophthalmology & visual science, 2010)
Achromatopsia (ACHM) is a congenital autosomal recessive cone disorder with a presumed stationary nature and only a few causative genes. Animal studies suggest that ACHM may be a good candidate for corrective gene therapy. Future implementation of this therapy in humans requires the presence of viable cone cells in the retina. In this study the presence of cone cells in ACHM was determined, as a function of age. The appearance and thickness of all retinal layers were evaluated by spectral-domain optical coherence tomography (SD-OCT) in 40 ACHM patients (age range, 4-70 years) with known mutations in the CNGB3, CNGA3, and PDE6C genes. A comparison was made with 55 healthy age-matched control subjects. The initial feature of cone cell decay was loss of inner and outer segments with disruption of the ciliary layer on OCT, which was observed as early as 8 years of age. Cone cell loss further progressed with age and occurred in 8 (42%) of 19 patients below 30 years and in 20 (95%) of 21 of those aged 30+ years. Retinal thickness was significantly thinner in the fovea of all patients (126 μm in ACHM vs. 225 μm in the control; P < 0.001) and correlated with age (β = 0.065; P = 0.011). Foveal hypoplasia was present in 24 (80%) of 30 patients and in 1 of 55 control subjects. ACHM is not a stationary disease. The first signs of cone cell loss occur in early childhood. If intervention becomes available in the future, the present results imply that it should be applied in the first decade.